2016
DOI: 10.3389/fimmu.2016.00495
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and Fetal Mechanisms of B Cell Regulation during Pregnancy: Human Chorionic Gonadotropin Stimulates B Cells to Produce IL-10 While Alpha-Fetoprotein Drives Them into Apoptosis

Abstract: Maternal immune tolerance toward the fetus is an essential requisite for pregnancy. While T cell functions are well documented, little is known about the participation of B cells. We have previously suggested that IL-10-producing B cells are involved in pregnancy tolerance in mice and humans. By employing murine and human systems, we report now that fetal trophoblasts positively regulate the generation of IL-10-producing B cells. We next studied the participation of hormones produced by the placenta as well as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
0
9

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(61 citation statements)
references
References 44 publications
2
50
0
9
Order By: Relevance
“…B cells were first observed in the placental bed of women early in gestation, which was confirmed by later studies . During early pregnancy, B cells are implicated in the mechanisms of maternal‐fetal tolerance . Decidual B cells modestly increase between 27 and 33 weeks of gestation followed by a slight decline at term .…”
Section: Introductionmentioning
confidence: 60%
“…B cells were first observed in the placental bed of women early in gestation, which was confirmed by later studies . During early pregnancy, B cells are implicated in the mechanisms of maternal‐fetal tolerance . Decidual B cells modestly increase between 27 and 33 weeks of gestation followed by a slight decline at term .…”
Section: Introductionmentioning
confidence: 60%
“…Prior studies revealed that AFP might play such important roles as pro‐angiogenesis, anti‐oxidation and immunoprotection on the maternal‐fetal interface . But the other study found that the offspring of AFP knockout mice were normal in both pre‐ and post‐natal stages .…”
Section: Discussionmentioning
confidence: 95%
“…Regulatory B cells (Bregs) are the B cells producing IL-10 under the influence of gonadotropins. Bregs are increased in early human pregnancy and suppress TNFα production by T cells (201,202). Maternal Tregs, stimulated by chorionic gonadotrophins, accumulate at the maternal-fetal interface during early gestation (203,204), peak in the second trimester (205), and mediate tolerance to paternal antigens, facilitating embryo implantation and preventing embryo resorption (206)(207)(208)(209).…”
Section: Maternal-fetal Tolerance and Tregsmentioning
confidence: 99%
“…Decidual B cells can secrete both pro-inflammatory IL-12 and IL-6, as well as immunosuppressive IL-35 (138) suggesting multiple context-dependent roles for B cells during intrauterine inflammation. Furthermore, CD19 + CD24 hi CD27 + B cells can produce IL-10 under the influence of gonadotropins, and these regulatory B cells (Bregs) are increased in early human pregnancy and suppress TNFα production by T cells (201,202). Additionally, adoptive transfer of IL-10 producing B cells increased the number of uterine Tregs and protected against LPSinduced adverse pregnancy effects by decreasing the production of IL-17A and IL-6 by naïve CD4 + CD25 − T cells (140).…”
Section: B Cellsmentioning
confidence: 99%